FACTORS ASSOCIATED WITH MATERNAL KNOWLEDGE ON EXCLUSIVE BREASTFEEDING IN CIPAYUNG SUB-DISTRICT, DEPOK CITY, INDONESIA - Alifani Faiz Faradhila; Sandra Fikawati (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Exclusive breastfeeding practice during six-months could reduce morbidity and mortality of mother and infant. This study aims to examine the sociodemographic characteristics as the the factors associated with knowledge among six-months exclusively breastfeeding mothers in Cipayung Sub-District, Depok City, Indonesia. Methods: This was a cross-sectional collected from 122 mothers with six-months exclusively breastfeeding. The participants selected through purposive sampling in Cipayung Sub-District in year 2017. Results: Only 80% mothers exclusively breastfeeding for six months. More than half mothers (59%) had high educational level, advance and tertiary. Most of mothers (91%) were unemployed. Approximately 22.1% mothers had high status of social economic. Eighty-two percent mothers who have children more than one. Six-months exclusively breastfeeding mothers who had high educational level were more likely has high knowledge than those with low educational level (p=0.010; OR=2.85; CI95%=1.34-6.06). Mothers who had low educational level were 2.85 times higher risk to have low maternal knowledge of exclusive breastfeeding compared with high educational level. Conclusions: Knowledge of exclusive breastfeeding among mothers was significantly associated to educational level. Interventions emphasizing practical education should therefore be targeted at addressing factors that associated knowledge of exclusive breastfeeding.